Analysis of Junior High School Students' Learning Media Preferences: Case Study in Bener Meriah Regency - Munawarah Munawarah; Nurul Khotimah; Anik Widiastuti; Agustina Tri Wijayanti (Jurnal Pemberdayaan Masyarakat, 2025)
Learning media play a vital role in enhancing students' understanding by transforming abstract concepts into concrete experiences, especially in today's technology-driven educational landscape. This study aims to analyze Junior High School students' preferences for learning media based on five indicators: learning modality, engagement and motivation, media effectiveness, technology and media use, and assessment preferences. Using a descriptive quantitative approach, data were collected through a four-point Likert scale questionnaire administered to 93 students across three Junior High Schools in Bener Meriah Regency. The findings reveal a strong preference for technology-based and multimodal learning media that integrate visual, auditory, and kinesthetic elements. Virtual laboratories were considered the most effective in facilitating concept comprehension, while multiple-choice tests were the most preferred form of assessment due to their objectivity and practicality. These results underscore the need for developing adaptive, interactive, and student-centered media that cater to diverse learning styles. This study contributes to the growing literature on media preferences by providing empirical insights that can help educators select more suitable learning tools and design inclusive instructional strategies. Such understanding is essential for improving student engagement, motivation, and academic achievement in 21st-century learning environments.